2020
DOI: 10.1182/bloodadvances.2020002553
|View full text |Cite
|
Sign up to set email alerts
|

Fractures are common within 18 months following first-line R-CHOP in older patients with diffuse large B-cell lymphoma

Abstract: Diffuse large B-cell lymphoma (DLBCL) and osteoporotic fracture are both more common in older patients. Exposure to R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisolone) is likely to increase the risk of fracture, but evidence is lacking to define fracture incidence in this group. Data on consecutive patients with DLBCL aged ≥70 years treated with 1 to 8 cycles of full or attenuated R-CHOP were retrospectively collected across 10 UK centers (2009-2019). Patients were followed up from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
3
11
1
Order By: Relevance
“…Our results are, to some extent, in agreement with other studies on osteoporosis and fractures in patients with hematologic malignancies and specifically lymphoma (132)(133)(134)179). Most of the studies published on osteoporosis or fractures in lymphoma patients hitherto have been small.…”
Section: Patients With Lymphomasupporting
confidence: 92%
See 3 more Smart Citations
“…Our results are, to some extent, in agreement with other studies on osteoporosis and fractures in patients with hematologic malignancies and specifically lymphoma (132)(133)(134)179). Most of the studies published on osteoporosis or fractures in lymphoma patients hitherto have been small.…”
Section: Patients With Lymphomasupporting
confidence: 92%
“…Our cohort was heterogenous, with a mixture of many lymphoma subtypes and included both treated and untreated patients. Additionally, we only included hip fractures while the studies from Denmark and UK included an "osteoporotic event" and all fracture types, respectively, which might partly explain the differences in our results (132,133). In Sweden, the use of rituximab in first line therapy of lymphoma started between 2003 and 2007 (181).…”
Section: Patients With Lymphomamentioning
confidence: 96%
See 2 more Smart Citations
“…Lymphoma patients were at a signi cant higher risk of an osteoporotic event with a 5-year cumulative rate 10%, in comparison with general population of 6.8% in Denmark [21] . Recently, a study from United Kingdom reported that receipt of R-CHOP in DLBCL patients were at a cumulative risk of 11.4% for bone fracture at 18 months older than 70 years old [22] . In China, an estimated prevalence of osteoporosis to be 6.46% for men and 29.13% for women aged ≥ 50 years [23] .…”
Section: Discussionmentioning
confidence: 99%